Optimizing energy efficiency in urban 5G wireless communication systems - HATİPOĞLU, Bünyamin and ACARER, Tayfun (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to optimize the energy efficiency of urban 5G networks by examining the influence of advanced antenna configurations and beamforming technology, addressing the growing need for reliable, high-speed, and energy-efficient communication in densely populated environments with the anticipated proliferation of IoT devices. A comprehensive methodology was adopted, combining literature review, qualitative analysis, and simulation-based evaluations in which transmitter power, carrier frequency, antenna height, and construction materials were systematically varied. Simulations analyzed the impact of these parameters on signal propagation, path loss, attenuation, and energy consumption, with special emphasis on the role of beamforming in enhancing performance. The findings indicate that optimized antenna configurations, coupled with beamforming, significantly improve received signal strength, reduce interference, and lower energy consumption, while variations in frequency, antenna height, and material type produce measurable differences in path loss, emphasizing the need for context-specific parameter tuning. The results conclude that strategic deployment of 5G infrastructure with optimized antenna and beamforming configurations can substantially improve energy efficiency and network performance in complex urban settings, supporting sustainable and high-quality connectivity. Practically, the study provides actionable guidelines for network engineers, policymakers, and telecommunications providers, highlighting the transformative potential of 5G in sectors such as healthcare, transportation, manufacturing, and defense while contributing to sustainable urban development.